منهج الإمام المزني في مسألة الإيمان من خلال كتابه شرح السنة دراسة مقارنة - عبدالله, أ.م.د. محمد حسين; عزيز, عزيز ستار (Sulaimani Journal for Humanities, 2023)
1- He (may Allah have mercy on him) defined faith in his book (Explanation of the Sunnah) according to the Sharia only, where he said: “Faith is to announce verbally and to act practically,” and in his definition he agreed with the doctrine of the predecessors and the people of Hadith. 2- He (may Allah have mercy on him) responded in his thesis, the doctrine of deferral from the Jahmiyyah, the Karamiyyah, and the Murji’ah jurists that act is a part of so-called faith and its reality , where he said: “There is no faith except with act, and no work except with faith.” Because the Murji’ah with its three sects believe that work is not included in so-called faith and reality of faith. 3- He (may Allah have mercy on him) emphasized that faith has branches and parts that it increases with obedience and decreases with disobedience, as he said: “And the believers differ in faith, and in good deeds they increase….” And this principle also agreed with the doctrine of the predecessors and the people of Hadith because they believe that faith increases with obedience and decreases with disobedience. 4- He (may Allah have mercy on him) responded by saying: “And the believers differ in faith, and in righteous deeds they increase….” There are two Islamic sects: the people of excess and extremism, and they are the threatening ones from the Kharijites and the Mu’tazilites, and the people of exceeding and negligence, and they are threating from the Jahmiyyah, the Karamiyyah, and the Murji’ah. jurists; Because both groups believe that faith is one and indivisible, and based on this, it is not increased by acts of worship, nor decreased by acts of disobedience.